On the multidimensional central limit theorem - Paulauskas, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Паулаускас. О многомерной центральной предельной теоремеV. Paulauskas. Apie daugiamatę centrinę ribinę teoremą